Effect of Internal Structure of Collagen/Hydroxyapatite Scaffold on the Osteogenic Differentiation of Mesenchymal Stem Cells - Chen, Guobao; Lv, Yonggang; Dong, Chanjuan; Yang, Li (Current Stem Cell Research & Therapy, 2015)
Consisting of seed cells and scaffold, regenerative medicine provides a new way for the repair and regeneration of tissue and organ. Collagen/hydroxyapatite (HA) biocomposite scaffold is highlighted due to its advantageous features of two major components of bone matrix: collagen and HA. The aim of this study is to investigate the effect of internal structure of collagen/HA scaffold on the fate of rat mesenchymal stem cells (MSCs). The internal structure of collagen/HA scaffold was characterized by micro-CT. It is found that the porosity decreased while average compressive modulus increased with the increase of collagen proportion. Within the collagen proportion of 0.35%, 0.5% and 0.7%, the porosities were 89.08%, 78.37% and 75.36%, the pore sizes were 140.6±75.5 μm, 133.9±48.4 μm and 160.7±119.6 μm, and the average compressive moduli were 6.74±1.16 kPa, 8.82±2.12 kPa and 23.61±8.06 kPa, respectively. Among these three kinds of scaffolds, MSCs on the Col 0.35/HA 22 scaffold have the highest viability and the best cell proliferation. On the contrary, the Col 0.7/HA 22 scaffold has the best ability to stimulate MSCs to differentiate into osteoblasts in a relatively short period of time. In vivo research also demonstrated that the internal structure of collagen/HA scaffold has significant effect on the cell infiltration. Therefore, precise control of the internal structure of collagen/HA scaffold can provide a more efficient carrier to the repair of bone defects.
Keywords: mesenchymal stem cells